2000
DOI: 10.1097/00006123-200011000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for Epilepsy Associated with Cavernous Malformation: Retrospective Study in 49 Patients

Abstract: This series is the first to specifically evaluate the capability of GK surgery to safely and efficiently treat epilepsy associated with CM. Seizure control can be reached when a good electroclinical correlation exists between CM location and epileptogenic zone. Although we do not recommend GK surgery for prevention of bleeding for a CM that has not bled previously, our findings suggest that GK surgery can be proposed for the treatment of epilepsy when the CM is located in a highly functional area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 21 publications
0
49
0
3
Order By: Relevance
“…Patients with simple partial seizures also had better outcomes than those presenting with complex partial seizures. 49 Surgical removal is considered the best treatment for patients with intractable seizures. Cappabianca et al 7 have shown that from among a series of 35 patients with solitary supratentorial CMs, 29 became seizure free (83%) after lesionectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with simple partial seizures also had better outcomes than those presenting with complex partial seizures. 49 Surgical removal is considered the best treatment for patients with intractable seizures. Cappabianca et al 7 have shown that from among a series of 35 patients with solitary supratentorial CMs, 29 became seizure free (83%) after lesionectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 3 largest studies conducted by Liscák et al, 35 Liu et al, 37 and Ré-gis et al, 49 only Liscák et al reported increased seizure frequency in 2 of 44 patients due to transient radiationinduced edema. In a study of 28 patients, Zhang et al 67 described 6 patients whose seizures increased in frequency.…”
Section: Seizure Controlmentioning
confidence: 96%
See 1 more Smart Citation
“…A cavernous malformation (CM) is a congenital vascular abnormality that can cause haemorrhage or neurological deficit but more commonly manifests as recurring seizures [54][55]. Although open microsurgical treatment of CM remains the standard efficacious therapy, a recent study by Regis, et al suggested a role for radiosurgery in the treatment of seizures associated with CM near the "highly functional cortex", a location that may preclude open resection [54].…”
Section: Cavernous Malformationmentioning
confidence: 99%
“…Although open microsurgical treatment of CM remains the standard efficacious therapy, a recent study by Regis, et al suggested a role for radiosurgery in the treatment of seizures associated with CM near the "highly functional cortex", a location that may preclude open resection [54]. Using a mean dose of 19 Gy, 53% of 49 patients with refractory seizures became seizure-free and 20% of treated ones improved at two years [54]. These results demonstrate that epilepsy associated with CM located near the eloquent cortex may be treated with radiosurgery to reduce seizure frequency.…”
Section: Cavernous Malformationmentioning
confidence: 99%